Measurements of t(t)over-bar spin correlations and top quark polarization using dilepton final states in pp collisions at root s=8 TeV - (:unkn) unknown (AMER PHYSICAL SOC, 2016)
Measurements of the top quark-antiquark (t (t) over bar) spin correlations and the top quark polarization are presented for t (t) over bar pairs produced in pp collisions at root s = 8 TeV. The data correspond to an integrated luminosity of 19.5 fb(-1) collected with the CMS detector at the LHC. The measurements are performed using events with two oppositely charged leptons (electrons or muons) and two or more jets, where at least one of the jets is identified as originating from a bottom quark. The spin correlations and polarization are measured from the angular distributions of the two selected leptons, both inclusively and differentially, with respect to the invariant mass, rapidity, and transverse momentum of the t (t) over bar system. The measurements are unfolded to the parton level and found to be in agreement with predictions of the standard model. A search for new physics in the form of anomalous top quark chromo moments is performed. No evidence of new physics is observed, and exclusion limits on the real part of the chromo-magnetic dipole moment and the imaginary part of the chromo-electric dipole moment are evaluated.
Keywords: PAIR PRODUCTION; DECAY